2010
DOI: 10.1186/1471-213x-10-12
|View full text |Cite
|
Sign up to set email alerts
|

Sex and the single embryo: early deveopment in the Mediterranean fruit fly, Ceratitis capitata

Abstract: BackgroundIn embryos the maternal-to-zygotic transition (MTZ) integrates post-transcriptional regulation of maternal transcripts with transcriptional activation of the zygotic genome. Although the molecular mechanisms underlying this event are being clarified in Drosophila melanogaster, little is know about the embryogenic processes in other insect species. The recent publication of expressed sequence tags (ESTs) from embryos of the global pest species Ceratitis capitata (medfly) has enabled the investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 44 publications
3
66
1
Order By: Relevance
“…These molecular data are consistent with previous very elegant genetic data which demonstrated that the female-promoting zygotic activity of Musca F gene (now Mdtra) depends on its maternal activity (Dubendorfer and Hediger 1998). Gabrieli et al (2010) showed that Cctra ep mRNAs are present in XX and in XY embryos, suggesting that there is no sex-specific early Cctra ep transcription. As the authors cannot discriminate between maternal and zygotic Cctra ep contribution, this issue is still open.…”
Section: History Of Drosophila Sex Determinationmentioning
confidence: 97%
See 2 more Smart Citations
“…These molecular data are consistent with previous very elegant genetic data which demonstrated that the female-promoting zygotic activity of Musca F gene (now Mdtra) depends on its maternal activity (Dubendorfer and Hediger 1998). Gabrieli et al (2010) showed that Cctra ep mRNAs are present in XX and in XY embryos, suggesting that there is no sex-specific early Cctra ep transcription. As the authors cannot discriminate between maternal and zygotic Cctra ep contribution, this issue is still open.…”
Section: History Of Drosophila Sex Determinationmentioning
confidence: 97%
“…Indeed in Drosophila it has been previously shown that early female-specific activation of the Sxl is achieved by a concentration threshold which will enable X-linked signalling elements to form active transcription complexes (Estes et al 1995). Gabrieli et al (2010) apparently proposed to transpose this model of Drosophila Sxl dose-sensitive transcriptional activation to the threshold-sensitive Ceratitis splicing activation of Cctra ep , based on their preliminary embryonal expression data. The most recent and in part novel sex determination model for Ceratitis capitata has been proposed by Salvemini et al (2009).…”
Section: History Of Drosophila Sex Determinationmentioning
confidence: 98%
See 1 more Smart Citation
“…At a very early stage of embryogenesis, sex determination is one of the main events in the Mother-to-Zygotic Transition (MZT) (Gouw et al 2009;Gabrieli et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the Ag mutation prevents the production of a sufficient supply of maternal tra F needed to activate the female mode of tra splicing. However, studies of precisely timed C. capitata embryos suggest that the presence of maternal tra RNA is not sufficient to lock female embryos into the female splicing mode [Gabrieli et al, 2010]. Taking advantage of the much slower development of medfly embryos (cellularization at 9-11 h compared to 2.10-2.35 h in D. melanogaster ), it was found that both male and female embryos contained several tra transcripts during the critical pre-cellular phase, including tra M and tra F .…”
mentioning
confidence: 99%